The Texas badge [large type] - Richards, Dusty (Richards, Dusty. Brandiron series., 2018)
Saddler County Sheriff Dell Hoffman is charged with bringing the perpetrators of these horrific crimes to justice, but even the toughest and most cunning lawman in Texas has his limits. With nothing to go on but five bloody bodies, a cracked safe, and an empty jail, Dell works the fringe of his sleepy western town--the forgotten, the invisible, those who often see without being seen. The more he learns, though, the more he wishes he could forget. In search of the truth, Dell finds himself pulled into an dark world of murder, deception, and brutality the likes of which he never imagined. Will he solve the most heinous crime in Texas history? Or will Dell's drive for justice lead him to an even greater tragedy for both himself and those he cares for most? --Amazon